Protocol for Development of the Indian Autism Screening Questionnaire: The Screening Version of the Indian Scale for Assessment of Autism - Chakraborty, Satabdi (Indian J Psychol Med, 2020)
INTRODUCTION: Autism is included as a certifiable disability in the Indian Rights of Persons with Disability Act, 2016. The Indian Scale for Assessment of Autism (ISAA), developed by the Government of India and mandated for certifying disability, is a detailed instrument that needs trained mental health experts and takes time to administer. The current project was planned to develop a simple, easy to use screening tool based on the ISAA to identify possible cases in the community. METHODS: The project is planned in three phases. During the first phase, data collected during the development of the ISAA (N = 433/436 children with autism) will be used to identify questions answered as frequently, mostly, and always. During the second phase, the psychometric properties of the screening tool based on these items will be evaluated among research participants recruited from hospitals and special schools (n = 100). In the third phase, the screening questionnaire will be administered in the community (n = 500). RESULTS: The most frequently answered questions will be selected for inclusion in the proposed screening tool. The number of items in the screening tool will be kept as few as possible, with yes or no responses DISCUSSION: Indian Autism Screening Questionnaire (IASQ) will be tested as a screening version of ISAA, which can be used by community health workers, teachers, or school counselors. The IASQ will not provide a diagnosis of autism. A positive screening result should be followed by a thorough assessment by a trained specialist. Analyzing the psychometric properties of the test can help ensure cost-effective screening of the community to identify autism.